Petrography and geochemistry for mafic and ultramafic rocks from Tonagh Island in the Napier Complex, East Antarctica: A preliminary report - Owada, Masaaki; Osanai, Yasuhito; Toyoshima, Tsuyoshi; Tunogae, Toshiaki; Hokada, Tomokazu; Crowe, Warwick A. (National Institute of Polar Research, 1999)
P(論文) The geology of Tonagh Island is divided into five geological units. The boundaries among the units are thrusts or shear zones. Tonagh Island is dominated by mafic to felsic layered gneisses. Metamorphosed ultramafic rocks are locally exposed. The dolerite dykes cut the host gneiss and the shear zone, and have chilled margins. Lithological features for mafic and metamorphosed ultramafic rocks on Tonagh Island are classified into the following nine types: 1) two pyroxene gneiss; 2) garnet-bearing two pyroxene gneiss; 3) brown hornblende two pyroxene gneiss; 4) biotite-bearing two pyroxene gneiss; 5) fine- grained garnet two pyroxene gneiss; 6) pyroxenite; 7) websteritic peridotite; 8) hornblende-bearing lherzolitic peridotite; and 9) dolerite. The fine-grained garnet two pyroxene gneiss occurs as dyke cutting the foliation and the layering of the host gneiss. The hornblende-bearing lherzolitic peridotites are considered to be intrusive rocks based on geological investigation. The MORE normalized trace element patterns of the dolerite and the fine-grained garnet two pyroxene gneiss are similar to those of the within-plate basalt. Some of the mafic gneisses and the metamorphosed ultramafic rocks have high MgO contents (up to 31 wt%), and are plotted in the komatiitic field on the (Fe_ +Ti)-Al-Mg diagram. The brown hornblende two pyroxene gneiss, the websteritic peridotite and the hornblende-bearing lherzolitic peridotite show similar REE patterns such as light REE enrichment. These geochemical features imply that original rock of some mafic gneiss and metamorphosed ultramafic rocks from Tonagh Island were Archaean komatiitic rock. departmental bulletin paper